2022
DOI: 10.18632/aging.204151
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m7G-associated lncRNA prognostic signature for predicting the immune status in cutaneous melanoma

Abstract: RNA modifications, including RNA methylation, are widely existed in cutaneous melanoma (CM). Among epigenetic modifications, N7-methylguanosine (m7G) is a kind of modification at 5' cap of RNA which participate in maintaining the stability of mRNA and various cell biological processes. However, there is still no study concerning the relationship between CM and m7G methylation complexes, METTL1 and WDR4. Here, long non-coding RNA (lncRNAs) and gene expression data of CM from the Cancer Genome Atlas (TCGA) datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For example, some researchers have identified that the m 7 G-related lncRNA risk model can be an efficient prognostic tool and anti-tumor immunotherapy target for multiple cancer types, including colon carcinoma, 34 Lung Adenocarcinoma 35 and cutaneous melanoma. 36 In our study, the m 7 G-related lncRNAs risk model was constructed using three prognostic lncRNAs by bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some researchers have identified that the m 7 G-related lncRNA risk model can be an efficient prognostic tool and anti-tumor immunotherapy target for multiple cancer types, including colon carcinoma, 34 Lung Adenocarcinoma 35 and cutaneous melanoma. 36 In our study, the m 7 G-related lncRNAs risk model was constructed using three prognostic lncRNAs by bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have analyzed the expression data of melanoma in the TCGA database and established a prediction model between immune-related lncRNAs and the survival status of melanoma ( 86 , 87 ). The analysis in TCGA database indicated that 6 differentially expressed m7G-related lncRNAs have been identified, and a prognostic model was constructed for predicting the tumor growth, metastasis and survival status of patients ( 88 ). Another study found that a number of glycolysis-correlated lncRNAs show pivotal clinical effects by oncogenic pathways such as EMT and immune-related regulation ( 89 ).…”
Section: Lncrnas In the Immune Microenvironmentmentioning
confidence: 99%
“…After reading and summarizing the published literature, 23 m7G regulatory factors were identified. The m7G regulatory factors include METTL1, WDR4, NSUN2, DCP2, DCPS, NUDT10, NUDT11, NUDT16, NUDT3, NUDT4, NUDT4B, AGO2, CYFIP1, EIF4E, EIF4E1B, EIF4E2, EIF4E3, GEMIN5, LARP1, NCBP1, NCBP2, NCBP3, EIF3D, EIF4A1, EIF4G3, IFIT5, LSM1, NCBP2 L, and SNUPN (Rong et al, 2022). A total of 16,773 lncRNAs were obtained in the OSCC data set of TCGA.…”
Section: Identification Of M7g-related Lncrnasmentioning
confidence: 99%